2021
DOI: 10.1080/1177083x.2021.1948873
|View full text |Cite
|
Sign up to set email alerts
|

In media we trust? A comparative analysis of news trust in New Zealand and other Western media markets

Abstract: In the age of misinformation, trust and trustworthinesscore values of journalismhave become more important as news companies reeling from the pandemic seek emergency funding for their operations from the public and funders look for trusted brands to support. Earlier studies indicated people are more willing to pay for trusted news brands, and recently, the public funding of news has been directed to institutions that are regarded as trustworthy news outlets, and provide information that is in the public intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…Brand Trust on Trustworthiness (H5) has a P value of 0.001, a C.R value of 7.702 and an estimate value of 0.676, which means that brand trust on trustworthiness has a positive significant relationship. This supports previous research this study has an effect of trust on brand trustworthiness (Myllylahti & Treadwell, 2022). The results of this study also support previous research, this study argues that perceived trustworthiness has a positive effect on news media brands (de Oliveira et al, 2022).…”
Section: Trustworthinesssupporting
confidence: 91%
See 1 more Smart Citation
“…Brand Trust on Trustworthiness (H5) has a P value of 0.001, a C.R value of 7.702 and an estimate value of 0.676, which means that brand trust on trustworthiness has a positive significant relationship. This supports previous research this study has an effect of trust on brand trustworthiness (Myllylahti & Treadwell, 2022). The results of this study also support previous research, this study argues that perceived trustworthiness has a positive effect on news media brands (de Oliveira et al, 2022).…”
Section: Trustworthinesssupporting
confidence: 91%
“…Trust has a positive effect on travel brand trust (Torres-Moraga & Barra, 2023). The same thing with this study found that trust has an influence on brand trust(Myllylahti & Treadwell, 2022).The conclusion drawn from the studies mentioned above is that Trustworthiness has a positive impact on Brand Trust. H5:…”
supporting
confidence: 85%
“…However, the perception of the reliability of such sources is also a location for unjust power relations. Though a source might have indicator-properties that signal trustworthiness and competence, it may not in fact be trustworthy and competent (Fricker 1999;Myllylahti and Treadwell, 2022).…”
Section: Hidden Power Relationsmentioning
confidence: 99%